Should I Seek Help for Sexual Difficulties? Middle-Aged Lebanese Women's Views. Issue 7 (30th September 2021) - Azar, Mathilde; Azar, Nagham; Kroll, Thilo; Bradbury-Jones, Caroline
Abstract: This qualitative study explored the way middle-aged Lebanese women address their sexual difficulties. Data analysis revealed three overarching themes and subthemes. From these we developed a help-seeking behavior framework for sexual difficulties. The framework focuses on: the perception of the problem, the beliefs about help-seeking and the sources of help. This framework can be used to facilitate access to personalized sexuality-related care based on a better understanding of the complex interplay of personal, socio-cultural and service-related factors that influence help-seeking behavior for sexual problems.